Caste, Costs and Educational Access in Rural Punjab (Journal of Education and Educational Development, 2020)
This paper is based on some key findings of an original research carried out to explore the issue of inequitable access to education within caste-based social structures in rural Punjab, Pakistan. Data from 36 interviews with low and high caste parents, school heads and four key informant focus groups in two villages in southern and central Punjab revealed that schooling costs remained difficult to manage for the poorest low-castes despite provision of government sponsored free schools. Bourdieu’s social critical framework used with specific reference to his notion of capitals reveals processes of social reproduction. The economic capital transubstantiates into social and cultural capital, refracting into schooling costs that are not just economic but also temporal, psychological and social for the lowest caste groups. This limits the impact of economic subsidies offered by the government for expanding educational access. The paper contributes to the current literature by arguing that policies aimed at equitable educational access must conceptualize educational costs as multidimensional, just as poverty itself is not just economic but multifaceted.